The known world - Bogen, Don. (Hanover, N.H. : University Press of New England, 1997)
Stunning poetry that explores the complex relationship between past and present.
Cover; Half title; Title; Copyright; Dedication; Contents; I; II; III
Print version record.
English.
eBooks on EBSCOhost
Keywords: American poetry; Poésie américaine.; POETRY -- American -- General; American poetry